Influência de complexos polipiridínicos de Ru(II) no processo de agregação do peptídeo beta amiloide - Cali, Mariana Pigozzi (Universidade Federal de São Carlos, 2023)
Most neurodegenerative diseases are associated with abnormal protein aggregation. Amyloid proteins are highly prone to aggregation and, consequently, accumulate in the brain, disrupting synapses and causing neurotoxicity. The work of this thesis aims to optimize the methodology and expression of recombinant Aβ as well as to investigate the theranostic potential of Ru(II) polypyridine complexes as luminescent probes and as inhibitors of the Aβ aggregation process. Aβ expression and purification was optimized based on the protocol developed by Abelein and collaborators. With this methodology, the Aβ40 and Aβ42 isoforms were obtained with a high degree of purity, high yield and with kinetic properties equivalent to the commercially available Aβ. The electronic absorption spectrum of the complexes in PBS buffer is characterized by an intense absorption band in the ultraviolet region typical of intraligand charge transfer transitions (ILCT) from the unsaturated aromatic ligands and by a broad absorption band in the visible region attributed to metal to ligand charge transfer transitions. The complexes have a maximum emission at 655 nm with a Stokes shift (separation between emission and excitation maxima) in the order of 5800 cm-1. The complexes containing the 3,4-diaminopyridine ligand also showed high antioxidant activity against the ABTS.+ radical. The effect of the complexes on Aβ aggregation was evaluated using nephelometry, which monitors the turbidity of the solution during protein aggregation. The Ru3,4Apy, RuMe3,4Apy and RuMe4Apy complexes exhibited lower relative nephelometry units (URNs) values when compared to the control, indicating the formation of fewer aggregates. In particular, the RuMe3,4Apy and RuMe4Apy complexes showed the greatest difference in relation to the control in the proportions 1:2.5 and 1:5 Aβ:complex. The analysis of the morphology of the species formed by transmission electron microscopy showed that Ru3,4Apy and Ru4Apy did not influence the morphology of the fibrils formed while the RuMe3,4Apy and RuMe4Apy complexes induced the formation of amorphous aggregates, by which the absence of secondary structure was confirmed by circular dichroism. The transgenic nematodes C. elegans (Caenorhabditis elegans), in which human Aβ42 is expressed in their muscle tissue, were used to evaluate the effect of the complexes in an in vivo model of Alzheimer's disease. For these studies, RuMe3,4Apy and Ru4Apy were chosen given their in vitro results. The two complexes improved the motility of the animals, indicating an anti-amyloid effect, as observed in vitro. Visualization of amyloid aggregates was performed by staining C. elegans nematodes with the amyloid dye X34, which is specific for amyloid fibrils. The nematodes that were treated with the complexes do not show the amyloid deposits as seen in the control, indicating that they showed an anti-amyloid effect not only in vitro, but also in vivo.
Influence of Ru(II) polypyridinic complexes on amyloid beta aggregation
Keywords: Doença de Alzheimer; Complexos de Rutênio; Peptídeo Beta Amilóide; Alzheimer's disease; Ruthenium Complexes; Amyloid Beta Peptide; CIENCIAS BIOLOGICAS::BIOFISICA::BIOFISICA MOLECULAR; CIENCIAS BIOLOGICAS::BIOQUIMICA::BIOLOGIA MOLECULAR; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::QUIMICA BIO-INORGANICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA